Current Techniques Used for Practical Blood Flow Restriction Training: A Systematic Review. Issue 10 (26th October 2021) - Bielitzki, Robert; Behrendt, Tom; Behrens, Martin; Schega, Lutz
Abstract: Bielitzki, R, Behrendt, T, Behrens, M, and Schega, L. Current techniques used for practical blood flow restriction training: a systematic review. J Strength Cond Res 35(10): 2936–2951, 2021—The purpose of this article was to systematically review the available scientific evidence on current methods used for practical blood flow restriction (pBFR) training together with application characteristics as well as advantages and disadvantages of each technique. A literature search was conducted in different databases (PubMed, Web of Science, Scopus, and Cochrane Library) for the period from January 2000 to December 2020. Inclusion criteria for this review were (a) original research involving humans, (b) the use of elastic wraps or nonpneumatic cuffs, and (c) articles written in English. Of 26 studies included and reviewed, 15 were conducted using an acute intervention (11 in the lower body and 4 in the upper body), and 11 were performed with a chronic intervention (8 in the lower body, 1 in the upper body, and 2 in both the upper and the lower body). Three pBFR techniques could be identified: (a) based on the perceptual response (perceived pressure technique), (b) based on the overlap of the cuff (absolute and relative overlap technique), and (c) based on the cuffs' maximal tensile strength (maximal cuff elasticity technique). In conclusion, the perceived pressure technique is simple, valid for the first application, and can be used independently of the cuffs' material properties, but is less reliable within a person over time. The absolute and relative overlap technique as well as the maximal cuff elasticity technique might be applied more reliably due to markings, but require a cuff with constant material properties over time.